A comparison of symptoms after the consumption of milk or lactose-hydrolyzed milk by people with self-reported severe lactose intolerance - Suarez, Fabrizis L; Savaiano, Dennis A; Levitt, Michael D (The New England journal of medicine, 1995)
Ingestion of a large dose of the milk sugar lactose--for example, the 50-g load in 1 liter of milk--causes symptoms such as abdominal pain, diarrhea, bloating, and flatulence in the majority of people with lactose malabsorption. It is uncertain whether the ingestion of more common doses of lactose, such as the amount in 240 ml (8 oz) of milk, causes symptoms. Some people insist that even smaller quantities of milk, such as the amount used with cereal or coffee, cause severe gastrointestinal distress. Methods. In a randomized, double-blind, crossover trial, we evaluated gastrointestinal symptoms in 30 people (mean age, 29.4 years; range, 18 to 50) who reported severe lactose intolerance and said they consistently had symptoms after ingesting less than 240 ml of milk. The ability to digest lactose was assessed by measuring the subjects' end-alveolar hydrogen concentration after they ingested 15 g of lactose in 250 ml of water. Subjects then received either 240 ml of lactose-hydrolyzed milk containing 2 percent fat or 240 ml of milk containing 2 percent fat and sweetened with aspartame to approximate the taste of lactose-hydrolyzed milk; each type of milk was administered daily with breakfast for a one-week period. Using a standardized scale, subjects rated the occurrence and severity of bloating, abdominal pain, diarrhea, and flatus and recorded each passage of flatus. Results. Twenty-one participants were classified as having lactose malabsorption and nine as being able to absorb lactose. During the study periods, gastrointestinal symptoms were minimal (mean symptom-severity scores for bloating, abdominal pain, diarrhea, and flatus between 0.1 and 1.2 [1 indicated trivial symptoms; and 2, mild symptoms]). When the periods were compared, there were no statistically significant differences in the severity of these four gastrointestinal symptoms.